Prognostic value of plasma adipokine chemerin in patients with coronary artery disease - Wang, Bo; Kou, Wenxin; Ji, Shuya; Shen, Rongrong; Ji, Hongwei; Zhuang, Jianhui; Zhao, Yifan; Li, Bo; Peng, Wenhui; Yu, Xuejing; Li, Hailing; Xu, Yawei (Frontiers in Cardiovascular Medicine, 2022)
Background Adipokine chemerin was proven to be associated with coronary artery disease (CAD), but its prognostic implications in CAD remain unclear. Methods This study consists of two parts, one is a basic study and the other is a clinical cohort study. First, we investigated the differential expression of six adipokines in the atherosclerotic mice model compared to mice with milder degrees of atherosclerosis and mice without atherosclerosis using microarray data. We then examined the potential of chemerin as a diagnostic and prognostic indicator in a CAD cohort. A total of 152 patients were enrolled in our study, including 77 patients with angiographically proven CAD and 75 control subjects without cardiovascular disease. Plasma adipokine chemerin levels were measured in all patients, and major adverse cardiovascular events (MACEs) were followed up, including ischemic stroke, non-fatal myocardial infarction, revascularization, and cardiovascular death. Results In the aortas of atherosclerotic mice, chemerin expression was up-regulated compared to control mice. The plasma chemerin levels of CAD patients were higher than those of non-CAD patients (128.93 ± 37.06 vs. 109.85 ± 27.47 mmol/L, respectively, P < 0.001). High chemerin levels were an independent predictor of CAD (β = 2.702, 95% CI, 1.344–5.431, P = 0.001). We followed up with patients for a median duration of 5.5 years (3.9–5.6). The Kaplan–Meier curves showed that patients in the high chemerin group had a significantly higher risk of MACEs than the low chemerin group in patients with CAD (log-rank P = 0.003), not with non-CAD (Log-rank P = 0.120). Furthermore, Cox multivariate analysis revealed that high chemerin levels were an independent predictor of MACEs (HR 2.267; 95% CI, 1.139–4.515; P = 0.020). Finally, the cellular study showed that chemerin is predominantly expressed in PBMC-derived macrophages. Conclusion Plasma chemerin levels were increased in the CAD patients, and a high chemerin level increased the risk of MACEs in CAD patients.